The Implementation of Teacher Performance in MTSS Sepakat Segenep - Meichaty, Alef; Novalina, Sesti; Pendi, Hamdi Zas; Putra, Dody; Syarifuddin, Amir (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This research aims to describe the implementation of teacher performance management at MTsS Sepakat Segenep. This type of research uses a qualitative approach with descriptive analytical study methods. Data collection used observation, interview and documentation study methods. Next, the data was analyzed using data reduction techniques, data presentation, and drawing conclusions. To test the validity of the data, data triangulation techniques were used. The results of this research conclude that the implementation of teacher performance management has been carried out by the madrasah as it should be. This can be seen from planning, implementation, monitoring and feedback in teacher performance management. The school has implemented a teacher performance improvement program at MTsS Sepakat Segenep. This was seen when the school held a performance planning meeting which was held a few days before the end of the school year. This is intended so that at the start of the school year the teachers will have implemented a work program without disrupting the new school year by formulating a work program. Then, in making decisions about school goals, the principal does so through deliberation so that teachers can provide input about the actual conditions in the field and what obstacles might arise. When the school's goals have been obtained, then the principal determines the concept of a work program which must then be developed into a work program by the teachers according to their respective duties and functions.